Design and Evaluation of an Electronic Override Mechanism for Medication Alerts to Facilitate Communication Between Prescribers and Pharmacists. (July 2015) - Russ, Alissa L.; Chen, Siying; Melton, Brittany L.; Saleem, Jason J.; Weiner, Michael; Spina, Jeffrey R.; Daggy, Joanne K.; Zillich, Alan J.
Background: Computerized medication alerts can often be bypassed by entering an override rationale, but prescribers' override reasons are frequently ambiguous to pharmacists who review orders.Objective: To develop and evaluate a new override mechanism for adverse reaction and drug-drug interaction alerts. We hypothesized that the new mechanism would improve usability for prescribers and increase the clinical appropriateness of override reasons.Methods: A counterbalanced, crossover study was conducted with 20 prescribers in a simulated prescribing environment. We modified the override mechanism timing, navigation, and text entry. Instead of free-text entry, the new mechanism presented prescribers with a predefined set of override reasons. We assessed usability (learnability, perceived efficiency, and usability errors) and used a priori criteria to evaluate the clinical appropriateness of override reasons entered.Results: Prescribers rated the new mechanism as more efficient (Wilcoxon signed-rank test, P = 0.032). When first using the new design, 5 prescribers had difficulty finding the new mechanism, and 3 interpreted the navigation to mean that the alert could not be overridden. The number of appropriate override reasons significantly increased with the new mechanism compared with the original mechanism (median change of 3.0; interquartile range = 3.0; P < 0.0001).Conclusions: When prescribers were given a menu-based choice for override reasons, clinical appropriateness of these reasons significantly improved. Further enhancements are necessary, but this study is an important first step toward a more standardized menu of override choices. Findings may be used to improve communication through e-prescribing systems between prescribers and pharmacists.